Concepto Bobath en niños con Parálisis Cerebral Infantil - Erazo Martínez, Camila Belén (2019)
The research work was developed in the modality of bibliographic review aiming to inform about the effectiveness of the Bobath concept as a treatment in children with cerebral palsy, since it is a method that helps us in the relaxation, facilitation and stimulation of normal movements, knowing that the Bobath concept is a specialized therapy applied to treat disorders of movement and posture. Although the Bobath concept is a novel technique in Latin America, it found 100 articles of which most had nothing to do with the subject or did not meet a rating of more than 5 according to the PEDro scale. The articles that have been taken into account that have been only 35 since they have a grade equal to or greater than 6, of which the majority are in the English language. The information on this technique applied in childhood cerebral palsy is minimal, so this research aims to add a quality study to existing ones. The databases in which the most search results were obtained with respect to the subject are: Pudmed, Scielo, Redalyc, PEDro, Scopus and ProQuest. The research project concludes that the effectiveness of the Bobath concept as a treatment in children with cerebral palsy is positive, since it improves and helps us in inhibiting abnormal movements by improving posture and avoiding long-term joint deformities.